Evidenciação do Valor Justo de Ativos Financeiros das Empresas Listadas na BM&FBovespa - Leandro Politelo (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2014)
This research aims to measure the level of disclosure of information relating to the fair value of financial instruments required by CPC 40 companies listed on the New Market segment of the BM&FBovespa. The study is characterized as descriptive and was conducted through documental analysis and quan - titative boarding. The population consists of 255 observations, with 127 companies in 2010 and 128 in 2011. The sample included 251 observations, with 125 firms in 2010 and 126 in 2011. The data collection was prepared a checklist consisting of 13 items, based on CPC 40. We used a content analysis of the notes of the years 2010 and 2011 of enterprises. The research results show that the disclosure mean of companies was 36.62% in 2010 and 40.35% in 2011. In both years there were companies that responded completely to the items discussed and companies that did not show any items. The sectors with the highest and lowest level of disclosure in the years 2010 and 2011 were, respectively, the sector of “Petroleum, Gas and Biofuels” and “Financial and Other”. It is concluded that the level of disclosure of companies in segment of New Market listed on the BM & FBovespa, spite of having presented an evolution in the analyzed period, may be considered low.